Nano-haemoglobin-based oxygen carrier increases the radiosensitivity of non-small-cell lung cancer - Changmin Liu; Yong Li; Shanhui Feng; Xiaoran Lv; Fengjuan Li; Binglou Wong; Jiaxin Liu; Chengmin Yang (Artificial Cells, Nanomedicine, and Biotechnology)
Haemoglobin-based oxygen carriers (HBOCs) could improve the hypoxic state of non-small-cell lung cancer (NSCLC) and increase radiotherapy sensitivity. We assessed the in vitro effects of nano-HBOC + irradiation therapy (IR) on NSCLC cells and the in vivo effect on a mouse model. H385 human NSCLC cell line was used to evaluate the nano-HBOC effect + IR on the cellular partial pressure of oxygen (pO2), cell activity and changes in reactive oxygen species (ROS) 1–2 h post-exposure. An NSCLC tumour-bearing mouse model was established to evaluate nano-HBOC+IR efficacy 28 d post-exposure. In vitro, pO2 tended to increase in nano-HBOC groups versus control, cell activity decreased (p < 0.01) and ROS level increased (p < 0.05). Post-irradiation, pO2 increased in nano-HBOC+IR groups versus control (p < 0.01), viability decreased (p < 0.01) and ROS increased (p < 0.01). No significant difference between nano-HBOC groups was observed. In vivo, nano-HBOC was most abundant at the tumour site and pO2 increased 6 h post-injection (p > 0.05). Tumour size was smaller in the IR and nano-HBOC+IR groups versus control. ROS levels and cell death were significantly increased. Nano-HBOC can improve pO2, enhance radiotherapy’s inhibitory ability on NSCLC cell lines and tumour-bearing mouse models, and promote ROS release.